KIAA0556 is a novel ciliary basal body component mutated in Joubert syndrome. Issue 1 (December 2015) - Sanders, Anna; de Vrieze, Erik; Alazami, Anas; Alzahrani, Fatema; Malarkey, Erik; Sorusch, Nasrin; Tebbe, Lars; Kuhns, Stefanie; van Dam, Teunis; Alhashem, Amal; Tabarki, Brahim; Lu, Qianhao; et al.
Abstract Background Joubert syndrome (JBTS) and related disorders are defined by cerebellar malformation (molar tooth sign), together with neurological symptoms of variable expressivity. The ciliary basis of Joubert syndrome related disorders frequently extends the phenotype to tissues such as the eye, kidney, skeleton and craniofacial structures. Results Using autozygome and exome analyses, we identified a null mutation inKIAA0556 in a multiplex consanguineous family with hallmark features of mild Joubert syndrome. Patient-derived fibroblasts displayed reduced ciliogenesis potential and abnormally elongated cilia. Investigation of disease pathophysiology revealed thatKiaa0556 -/- null mice possess a Joubert syndrome-associated brain-restricted phenotype. Functional studies inCaenorhabditis elegans nematodes and cultured human cells support a conserved ciliary role for KIAA0556 linked to microtubule regulation. First, nematode KIAA0556 is expressed almost exclusively in ciliated cells, and the worm and human KIAA0556 proteins are enriched at the ciliary base. Second, C. elegans KIAA0056 regulates ciliary A-tubule number and genetically interacts with anARL13B (JBTS8 ) orthologue to control cilium integrity. Third, human KIAA0556 binds to microtubules in vitro and appears to stabilise microtubule networks when overexpressed. Finally, human KIAA0556 biochemically interacts with ciliary proteins and p60/p80 katanins. The latter form a microtubule-severing enzyme complex that regulates microtubule dynamics as well as ciliary functions. Conclusions We have identified KIAA0556 as a novel microtubule-associated ciliary base protein mutated in Joubert syndrome. Consistent with the mild patient phenotype, our nematode, mice and human cell data support the notion that KIAA0556 has a relatively subtle and variable cilia-related function, which we propose is related to microtubule regulation.